Glucometric assessment of gingival crevicular blood in diabetic and non-diabetic patients: A randomized clinical trial - Puja Debnath; Vivek Govila; Mona Sharma; Ashish Saini; Suraj Pandey (Journal of Oral Biology and Craniofacial Research)
Background: Diabetes mellitus is one of the most incessant metabolic afflictions with high prevalence rate in Indians. Diagnosis of diabetics in the initial stage helps to prevent its long term complications that are responsible for high morbidity and mortality. The aim of the present study was to assess whether glucometric analysis using Gingival Crevicular Blood (GCB) can be used for screening of diabetic patients in dental chair. Materials and methods: Present study was a double blinded randomized controlled trial. A total of 50 patients, 25 diabetic and 25 non-diabetic with chronic periodontitis were enrolled in the study. Blood oozing from the gingival crevices after periodontal pocket probing of anterior teeth and Finger Prick Blood (FPB) was taken and analysed by glucometer. Result: Mean ± S.D was 195.84 ± 27.19 and 138.78 ± 29.95 for GCB and FPB respectively in diabetic group. For non-diabetic group Mean ± S.D was 103.84 ± 12.56 and 84.36 ± 10.36 respectively for GCB and FPB. A Karl Pearson correlation coefficient value of r = +0.735 for diabetic and r = +0.802 for non-diabetic group comparing GCB and FPB. Conclusion: GCB cannot be used for screening blood glucose during periodontal examination.